Personality Development Training Siswa SMK Muhammadiyah 1 Gresik dalam Menghadapi Modernisasi Industri - Moch Nuruddin; Akhmad Wasiur Rizqi; Misbah; Ahmad Fauzal Ibnu Amalik; M. Fauzan Eksando Pramaisyah (BADAN PENERBIT STIEPARI PRESS, 2025)
The Industrial Revolution 4.0 requires human resources who are not only technically competent but also capable of adapting to the rapidly changing dynamics of professional life. This transformation demands strong job readiness from vocational school graduates (SMK), as they are prepared to directly enter the industrial world. Students of Muhammadiyah 1 Vocational School in Gresik are an important target of this community service program, as their job readiness is a key factor in facing the intense competition in the era of industrial modernization. The main objective of this activity is to evaluate the effectiveness of personality development training in improving students’ job readiness. The training does not only focus on technical skills but also emphasizes soft skills such as communication, discipline, teamwork, and critical thinking. Through this approach, students are expected to gain a dual advantage: strong vocational expertise as well as a personality built on integrity. In addition, this activity examines the application of a positive discipline approach as an alternative to traditional disciplinary practices that often result in negative consequences, such as decreased learning motivation and weakened relationships between teachers and students. Positive discipline is considered more effective in shaping character because it emphasizes appreciation, responsibility, and self-awareness rather than punishment alone. This program applies a qualitative descriptive method, using observation, interviews, and analysis of students’ behavioral changes after participating in the training. The findings indicate that personality development training, combined with the application of positive discipline, significantly impacts students’ job readiness. They become more confident in facing the challenges of the workforce while also demonstrating improved discipline, independence, and integrity. In conclusion, personality development training and positive discipline are proven to be effective strategies in preparing young generations to comprehensively face the challenges of the Industrial Revolution 4.0..